Routine versus clinically indicated use of chest X-rays in patients presenting with ST-elevation myocardial infarction. (14th October 2021) - Leelo, N; Mortimer, N; Townend, J N; Doshi, S N; Nadir, M A
Abstract: Background: National Institute of Clinical Excellence (NICE) guidelines recommend consideration of Chest X-rays (CXRs) in patients presenting with chest pain to exclude non-cardiac causes of chest pains. However, patients with ST-segment elevation myocardial infarction (STEMI) have a clear diagnosis, rendering the rationale for routine CXRs in this cohort of patients unclear. However, this remains a common practice across the health service. Methods: We performed a retrospective study use of CXRs in consecutive patients admitted with STEMI undergoing primary percutaneous coronary intervention in a single UK tertiary cardiac center. We aimed to investigate if CXRs added clinical and diagnostic value by comparing routine vs. clinically indicated use. Results: A total of 122 patients (Mean Age 63±12, 87% Male) were admitted with STEMI during the study period and 114/122 (93.4%) patients received at least one CXR during their in-patient stay. All but 2/114 were portable thus resource-intensive. Of these, 75/114 (65.8%) were routine while 39/114 (34.2%) were clinically indicated. Although CXRs were performed in almost all the patients, only 56/114 (49.1%) of patients had the findings of CXRs documented in the clinical records. The diagnostic efficacy for CXR abnormalities was significantly higher in the clinically indicated CXR group (76.9%) rather than the routine CXR group (2.7%) (p=<0.001). The therapeutic efficacy was 53.8% for clinically indicated CXRs, whereas the routine CXRs had a therapeutic efficacy of 1.3% (p=<0.001). There was a significant association between CXR findings and whether the CXR requested was routine or not (χ 2 (1)=70.07, p<0.001) and also management changes (χ 2 (1)=45.43, p<0.001). Conclusions: Routine CXR in patient admitted with STEMI are often unnecessary and may add very little clinical value. On the other hand, selective post-procedural CXRs have a significantly higher diagnostic and therapeutic yield. Our study questions the rationale behind routine CXRs in the care of patients with STEMIs. Funding Acknowledgement: Type of funding sources: None.